"A positive guiding hand": A qualitative examination of youth-initiated mentoring and the promotion of interdependence among foster care youth. (October 2018) - Spencer, Renée; Drew, Alison L.; Gowdy, Grace; Horn, John Paul
Abstract: This qualitative interview study examined experiences of youth-initiated mentoring relationships (YIM) among youth transitioning out of the foster care system. YIM is an innovative approach wherein programs work with youth to identify adults within their existing social networks to serve as their mentors in the formal program. Participants were 13 mentor-youth dyads involved in a pilot trial of YIM in a mid-western city. Youth and mentors completed one-time, in-depth individual interviews. Narrative thematic analysis of the interview data yielded the following major findings: (a) youth overwhelmingly reported having a strong or very strong relationship with their mentor, (b) these relationships offered a number of forms of social support to the youth (i.e., appraisal, companionship, emotional, informational, and instrumental), and (c) the mentor was perceived to have positively impacted the youth during the course of the relationship in multiple ways, including the youth's psychological well-being, relationships with others, and beliefs about and orientation toward the future. These findings suggest that YIM is a promising approach for establishing meaningful and impactful connections that may promote interdependence for older foster care youth as they make the transition to adulthood. Highlights: In youth-initiated mentoring (YIM) youth identify adults they know to become their formal mentors. This study examined YIM relationships among youth transitioning out of foster care. Participants reported quickly building strong connections they expected to endure. In all cases, mentors provided multiple forms of support tailored to youth needs. For most, mentors helped youth sustain connections with other important people too.